2020
DOI: 10.3389/fimmu.2019.03123
|View full text |Cite
|
Sign up to set email alerts
|

High Cytotoxic Efficiency of Lentivirally and Alpharetrovirally Engineered CD19-Specific Chimeric Antigen Receptor Natural Killer Cells Against Acute Lymphoblastic Leukemia

Abstract: Autologous chimeric antigen receptor-modified (CAR) T cells with specificity for CD19 showed potent antitumor efficacy in clinical trials against relapsed and refractory B-cell acute lymphoblastic leukemia (B-ALL). Contrary to T cells, natural killer (NK) cells kill their targets in a non-antigen-specific manner and do not carry the risk of inducing graft vs. host disease (GvHD), allowing application of donor-derived cells in an allogenic setting. Hence, unlike autologous CART cells, therapeutic CD19-CAR-NK ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 61 publications
0
76
0
Order By: Relevance
“…Similar high gene transfer rates to primary NK cells were reached using Vecotfusin-1 as an enhancer, which might even be increased when using a different viral envelope. For Vectofusin-1, it was recently demonstrated that transgene delivery to primary NK cells can be improved by pseudotyping LVs with the envelope protein from endogenous feline virus (RD114) or baboon endogenous retrovirus (BaEV) instead of VSV-G ( 5 , 6 ). In the field of CAR T-cells gamma-retroviral vectors or VSV-G pseudotyped LVs are most commonly used for their generation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar high gene transfer rates to primary NK cells were reached using Vecotfusin-1 as an enhancer, which might even be increased when using a different viral envelope. For Vectofusin-1, it was recently demonstrated that transgene delivery to primary NK cells can be improved by pseudotyping LVs with the envelope protein from endogenous feline virus (RD114) or baboon endogenous retrovirus (BaEV) instead of VSV-G ( 5 , 6 ). In the field of CAR T-cells gamma-retroviral vectors or VSV-G pseudotyped LVs are most commonly used for their generation.…”
Section: Discussionmentioning
confidence: 99%
“…Transduction efficiencies of NK cells vary tremendously depending on the cell source, the viral vector system, and the transduction enhancer used ( 4 ). Lentiviral vectors (LVs) pseudotyped with the glycoprotein of the vesicular stomatitis virus (VSV-G) are classically used to generate CAR T-cells but are less efficient for NK cells with transduction efficiencies of 20–40% ( 5 , 6 ). Therefore, optimization of gene transfer protocols for VSV-G pseudotyped LV for the generation of CAR NK cells is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…73 The use of poly-L-lysine and DEAE-dextran has only been reported in a few NK cells transduction studies. 91 We and others showed enhanced viral transduction efficiency for CAR-NK cells with not only Retronectin, 88,92 but also Vectofusion-1, which has been reported as a promising alternative transduction enhancer. 93 Our data showed that Vectofusin-1 was as effective as Retronectin using VSV-G-pseudotyped LV, but demonstrated higher transduction efficiency for the RD114-TR-pseudotyped α-RV.…”
Section: Generation Of Car-nk Cellsmentioning
confidence: 94%
“…86,87 Recently, we and others demonstrated the dependency of the resulting transduction efficiency on the pseudotyping as RD114-TR-or Baboonpseudotyped lentiviruses transduced NK cells via the surface entry receptor ASCT2 that is upregulated following cytokine stimulation. 88,89 In addition, different transduction enhancers have been tested to increase the viral transduction efficiency of NK cells (e.g., polybrene, Retronectin, protamine sulfate, poly-L-lysine, DEAE-dextran, Vectofusin-1). The cationic polymers protamine sulfate and polybrene reduce the viral repulsion of NK cells, thereby enhancing the membrane fusion.…”
Section: Generation Of Car-nk Cellsmentioning
confidence: 99%
“…BaEV-LVs were shown to generate functional CAR expressing NKs. Another study also showed high-level CAR delivery into NK cells employing an alpha-retroviral vector system [ 54 ]. These results will pave the way to move CAR NK cell therapy into the clinic.…”
Section: Introductionmentioning
confidence: 99%